ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA USAHA DAGANG MEGAH MAKMUR FURNITURE DI TANJUNG REDEB (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
The purpose of this study is to find and analyze whether the cash accounting information system applied in UD stately prosperous furniture were accurate according to the accounting theory. Data analysis that used in this research was descriptive. Analysis technique with data and information collection and analysis done by information on the cash accounting information system according to the interviews and documentation, studies and review the data and information about the cash, outlines the cash accounting system in accordance with a literature study that is. Based on the result of the research by writer to know and analyze that information system accounting sales cash applied in UD Megah Makmur Furniture di Tanjung Redeb we root whose theories learned and the outline performed on chapters before, the writers can take conclusion that the cash sales in UD Megah Makmur Furniture has been good enough .This is proven by: a) the piece that responsible for duty, b) the documents that used, c) a note that used, d) a network of procedure, e) flowcharts, f) the division of authority.